Gender equality in Malaysia: the inconsistencies between the principle and its application / Diyana Sulaiman and Mazlina Ghazali - Sulaiman, Diyana; Ghazali, Mazlina (2005)
The dissertation primarily deals with the issue of the inconsistencies of the established laws (referring to the statutory provisions) with the principle of gender equality, as embedded in Article 8 of the Federal Constitution of Malaysia. Thorough discussion on loopholes of the law is provided, as well as other factors which give rise to inconsistencies between principle of equality and its application. Previous studies by other researchers which gave a clear picture on development of the law on gender equality before and after amendment of Article 8 (2) of the Federal Constitution are included. Real life problems where women are being discriminated against are included in our findings. Decided cases, statistics and interviews conducted are enclosed to support our findings. The dissertation has specifically addressed the issue of gender equality itself with the objective to handle this matter effectively. Therefore the current position of women and identified statutory provisions which are discriminatory in nature are analyzed. The dissertation calls for a greater urgency to reform the statutory provisions which undermine the principle of gender equality, to uphold woman's position in the society. Furthermore, it requires changes to the educational system in Malaysia. The writers urge that ancient thinking of the society that women can be discriminated against be wiped away, and be replaced by civilized modern way of thinking in which everyone must be treated equally.